Hybridity and Ambivalence in Abe Tomoji’s Shi no Hana - Shobichatul Aminah; Ratna Juwita; Gratia Herdina Kumaseh (Universitas Diponegoro, 2020)
This study aims to describe the hybridity and ambivalence in Abe Tomoji's novel, Shi no Hana, using postcolonial perspective. Shi no Hana describes the author's experience when he was a member of the Propaganda Troop on Java Island with a spatial setting in Batavia and Selekta (Malang). The time setting in this novel is during the Japanese occupation of Indonesia. This study examined the interaction between colonizers and colonized in the framework of Homi K. Bhabha's postcolonialism, which results in hybridity and ambivalence in the characters. In this study, the characters are identified and categorized based on their position as colonizer or colonized. In many kinds of research on postcolonial literary, the relationship between East and West, or between colonizer and colonized is seen as a hierarchical relationship where one party oppresses the other. However, this research does not merely look at the colonizer and colonized as a hierarchical relationship. This study found that hybridity and ambivalence can be seen through the depiction of characters who occupy the position of the colonizer and colonized at the same time.